OsRGA1 optimizes photosynthate allocation for roots to reduce methane emissions and improve yield in paddy ecosystems. (September 2021) - Chen, Yun; Zhang, Yajun; Li, Siyu; Liu, Kun; Li, Guoming; Zhang, Dongping; Lv, Bing; Gu, Junfei; Zhang, Hao; Yang, Jianchang; Liu, Lijun
Abstract: Rice cultivars influence methane emissions from paddies; however, which plant traits account for this effect and the corresponding mechanisms are poorly understood. A meta-analysis of data from the past 30 years was conducted to reveal the separate relationships of methane emissions from paddy fields with rice roots and N-application rates. A four-year field trial was designed to identify the key role of the rice G-protein α-subunit gene OsRGA1 in photosynthate allocation to roots and methane emissions with two rice cultivars, wild-type Yangdao 6 and mutant rga1 . The results of the meta-analysis suggested that an increase in root biomass would downregulate methane fluxes with an estimated effect size of −15.7% and that nitrogen application increased cumulative methane emissions by 8.4% during the latest decade. The ratio of nonstructural carbohydrates in roots to total organic carbon in exudates (NSC/TOC) might be the major index driving the differences in CH4 emissions among rice cultivars. OsRGA1 functioned in the allocation of photosynthates between root growth and rhizodeposition. The NSC/TOC ratio of the mutant rga1 was 36% lower than that of Yangdao 6, and belowground biomass was lower but root exudate quantity was greater, resulting in 22% higher methane emissions and 59% lower yield. Wild-type Yangdao 6 with higher nitrogen-use efficiency allocated more photosynthates for anabolic processes, thereby contributing to a vigorous root system and alleviating the inhibitory effects of nitrogen on methanotrophs, which led to low emissions and high rice production. Genetic improvement focusing on rice roots and nitrogen input effects as modulated by OsRGA1 may help develop strategies to simultaneously improve rice yield and decrease methane emissions. Highlights: Allocation of assimilate in roots drives the difference in CH4 emissions among cultivars. Greater storage of photosynthates in roots mitigates CH4 emissions and improves yield. OsRGA1 synergizes with C and N cycling in the rhizosphere, which benefits CH4 mitigation.